Strategi Komunikasi Customer Service Officer Bank Central Asia KCU Kelapa Gading Dalam Meningkatkan Nilai Branch Service Quality - Stevany; Satya Candrasari (UNIVERSITAS KALBIS, 2022)
Banking competition is getting tighter so that each bank focuses on service communication strategies to provide good service for customers. In this case study, PT Bank Central Asia Tbk KCU Kelapa Gading has an annual service quality assessment. In 2018-2019, the value of branch service quality decreased. This research uses communication strategy theory with qualitative methodology and descriptive case studies. Data were obtained by using observation techniques, in-depth interviews with informants from PT Bank Central Asia, Tbk KCU Kelapa Gading, literature studies, and documentation studies. The results of this research discuss customer service communication strategies in serving customers which include how to deliver messages, selection of communication media, methods of delivering messages and grouping customer categories. From the implementation of this communication strategy, customer service can get a value of 5 (very satisfied). Suggestions from the research are expected to maintain a very satisfied value and improve facilities at the branch.